Gambaran Serum Elektrolit Pada Pasien Acute Miocard Infark (AMI) Di Ruang Intensive Cardiovaskuler Care Unit (ICVCU) RSUD Dr. Moewardi Di Surakarta - Rahmadhani Nuzul Putri; Suryanti Suryanti; Siti Lestari (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background: AMI is a myocardial necrosis caused by inadequate blood supply.The cardiac muscle contractility has very important role in pumping blood. Contraction of the heart in pumping blood is regulated by cardiac action potential,such as role is sodium (Na +) and potassium (K +). AMI is a myocardial necrosis caused by inadequate blood supply. Objective of this research to describe the serum electrolytes such as sodium (Na +) and potassium (K +) in patients with AMI who undergoes treatment in ICVCU of Regional General Hospital Dr. Moewardi Surakarta in 2016.Reasearch Methods: This research uses descriptive research. The subject of this research is the patients who is treated in ICVCU of Dr. Moewardi hospital with Acute Myocardial Infarction a number of 57 respondents. The researh was conducted in two months. The sampling techniques is by total sampling. The data collection method uses observation technique. Results: The average of AMI respondents are 41-60 years old in which as much as 57.9%, male respondents are as much as 75.4%, the highest classification of AMI STEMI are 75.4%, the majority of respondents whose the results of sodium levels are in <136 mmol / L (low) are 71.9%, the result of potassium levels which are between 3.3 to 5.1 mmol / L (normal) are 82.5%. Conclusion: Average AMI patients are 41-60 years, the majority of respondents is male with the highestclassification of AMI STEMI and have the level of sodium is <136 mmol / L (low)